Digital literacy of physical education teachers in the 5.0 era - S., Adi; Soegiyanto; Rohidi, Tjetjep Rohendi; Rustiadi, Tri (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
Digital literacy is a factor that determines a teacher’s technology usage in learning. An interesting situation is found when physical education must be conducted in contemporary style, but on the other hand, it must also be able to incorporate practice in the field. This study aimed to investigate the digital literacy level of physical education teachers. The sample in this study was high school teachers in Bojonegoro Regency, consisting of 12 physical education teachers. The sample selection technique used was total sampling. The type of this research is quantitative using a survey method. Data was collected using a questionnaire via Google Form. After the data were obtained and grouped, they were then analyzed using percentages. The outcome of this research was organized into three categories, respectively the low category of 25.06%, the medium one of 33.34%, and lastly the high category of 41.6%. Young teachers fill the high category in the level of digital technology usage. From the results of the Spearman test, the younger the teacher, the better the level of mastery in technology. The computer literacy of physical education teachers affects their use of technology in delivering learning. Several things are related to one another, namely digital literacy, signals, and internet usage.